The Effect of Ethnocentrism and Product Knowledge on The Buying Interest of “Tembe Me’e Donggo”Products - Sri Ernawati (Universitas Muhammadiyah Mataram, 2018)
This current research explores the effect of ethnocentrism and productnowledge on the buyinginterest of the products ofTembe Mee Donggo. The research aims: 1) to determine the positive and significant effect of ethnocentrism on buying interest in tembe me’e Donggo products; 2) to determine the positive and significant effect of productknowledge on buying interest intembe me’e Donggo products; and 3) to determine the positive and significant influence of ethnocentrism and productknowledge on buying interest intembe me’e Donggo products. The methodology used in this research is associative in nature, using questionnaires, observations, and library research to collect data, and a multiple linear regression analysis to analyze the data. The research took place in Donggo district of Bima regency during the two months of February and March of 2018. The sample, taken using purposive sampling technique,include50 people of Donggo, who had ever used and bought tembe me’e Donggo products. The results reveal that: 1) ethnocentrism has a positive and significant effect on the buying interest of tembe me’e Donggo products; 2) product knowledge has a positive and significant effect to the buying interest of tembe mee Donggo products; and 3) ethnocentrism and product knowledge together have a positive and significant effect on the buying interest of tembe me’e Donggo products.